Research in Computational Molecular Biology: 20th Annual Conference, RECOMB 2016, Santa Monica, CA, USA, April 17-21, 2016, Proceedings - Singh, Mona (Lecture Notes in Computer Science, 2016)
Thisbook constitutes the proceedings of the 20th Annual Conference on Research inComputational Molecular Biology, RECOMB 2016, held in Santa Monica, CA, USA, inApril 2016.The 15 regular papers presented in this volume were carefullyreviewed and selected from 172 submissions. 20 short abstracts are included inthe back matter of the volume. They report on original research in all areas ofcomputational molecular biology and bioinformatics.